4R practices for fertilizer management in potatoes. Issue 2 (21st March 2019) - Flis, Sally
Abstract : Phosphorus is a key nutrient for the development of the potato plant and tubers. The status of P in the plant, deficient or sufficient, is closely related to yield. With the high value of a potato crop and the influence of proper phosphorus nutrition on plant and tuber development, the 4Rs and especially timing of phosphorus availability are critical to maximizing yield per acre. Earn 0.5 CEUs in Nutrient Management by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/676 .